2019
DOI: 10.1371/journal.pone.0210693
|View full text |Cite
|
Sign up to set email alerts
|

Client satisfaction with existing labor and delivery care and associated factors among mothers who gave birth in university of Gondar teaching hospital; Northwest Ethiopia: Institution based cross-sectional study

Abstract: BackgroundThere are many reasons for mothers not receiving modern obstetric care, being dissatisfied by health care deliveries is one of the major factors. There are limited studies about maternal satisfaction with labor and delivery care services in Ethiopia and particularly in the study area. Therefore, the aim of this study was to better understand client satisfaction on existing labor and delivery care service and associated factors among mothers who gave birth in the University of Gondar Teaching Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
50
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 37 publications
8
50
5
1
Order By: Relevance
“…One study found that vaginal delivery offered more satisfaction based on WOMBLSQ than instrumental or cesarean delivery [12]. Similar findings have been reported by other studies [69,72,73,76]. In contrast, one study found that delivery via cesarean section offered higher labor satisfaction [77].…”
Section: Plos Onesupporting
confidence: 69%
See 1 more Smart Citation
“…One study found that vaginal delivery offered more satisfaction based on WOMBLSQ than instrumental or cesarean delivery [12]. Similar findings have been reported by other studies [69,72,73,76]. In contrast, one study found that delivery via cesarean section offered higher labor satisfaction [77].…”
Section: Plos Onesupporting
confidence: 69%
“…One study found that comorbidities like HIV, hypertension, and diabetes mellitus are associated with a 3.1% decrease in labor satisfaction [69]. The absence of comorbidity has a positive influence on maternal satisfaction [70]. This information will help in planning and implementing patient-centered care during labor and postnatal to improve maternal satisfaction.…”
Section: Plos Onementioning
confidence: 99%
“…Concerning sample size, the sample size of the individual studies ranged from 256 to 736. The highest and lowest prevalence (95%) and (19%) of women satisfaction towards existing labour and delivery services were reported in studies conducted in Wolaitta Soddo Town, Southern Nations, Nationalities, and Peoples Region and Addis Ababa, respectively [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] (table 2).…”
Section: Resultsmentioning
confidence: 99%
“…A recent review of literature on women's' satisfaction with maternal care in developing countries has observed that majority of studies have reported a high level of satisfaction (22). However, in several studies, clients have rated the quality of institutional maternal care as poor (24,25) which have been attributed by some authors to poor quality of health delivery systems, client characteristics such as literacy level, cultural diversity, and techniques of assessment of satisfaction.…”
Section: Discussionmentioning
confidence: 99%